Methodological approaches to assessing and forecasting the tax potential of the region - et. al., Tokhir Malikov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research paper describes o of methods and problems of forecasting tax budget revenues, taking into account the specifics of the Uzbekistan situation, is presented. Particular attention is paid to the use of time series techniques, discussion of issues related to benchmarking, "edge effects", the need to identify the structural and market components of tax revenues. It is concluded that the objective limitation of constructing correct and reliable long-term predictions of tax revenues is the lack of sufficiently long time series of comparable data. The forecasting horizon should correspond to the period during which trends are identified and estimates of dynamics parameters are made. In this regard, the use of the developed traditional econometric methods of analysis turns out to be impossible for long-term tax planning. For short-term forecasts, the necessary information is available, and they can be useful in the practical planned work of state bodies.